Influence of Capital Adequacy Ratio, Financing Risk, Cost Efficiency, Liquidity and Net Interest Margin on Profitability at BNI Syariah Period 2011-2019 - Zahrul Makarim Sulthony; Qi Mangku Bahjatulloh (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
The purpose of this research is to test and analyze the influence of capital adequacy ratio, financing risk, cost efficiency, liquidity and net interest margin towards profitability in BNI Sharia Bank period 2011-2019, the number of samples in this study is the reason for using Bank BNI Syariah as a sample of this research: Bank BNI Syariah operates in Indonesia in 2011-2019 and registered with Bank Indonesia (BI). Bank BNI Syariah publishes Trwiulannan financial statements in full and publish in the period 2011-2019. Data analysis uses multiple linear regression to test and prove research hypotheses, research results show capital adequacy, liquidity and net interest margins against profitability have no effect on the profitability evidenced by the significance of those variables more than 0.05. While financing risks and cost efficiencies have significant effect on profitability because of the significance of those variables less than 0.05. The magnitude of the effect of the predictor variable on profitability using the coefficient of determination obtained by 66.9% while the remaining33.1% is influenced by other variables outside this research model.